The crucial roles of nociceptin opioid peptide (NOP) receptor in attenuating relapse in morphine/methamphetamine (poly-drug) dependence model - Ridzwan, Irna Elina; Abdul Rahman, Nor Akhi Hijriyati; Wasli, Nur Syafinaz (2018)
BACKGROUND: Effective treatment for relapse prevention to poly-drug is still not yet available although this public health issue is alarming. Our previous study has proved that a combination of buprenorphine/naltrexone treatment successfully attenuated relapse (reinstatement) in morphine/methamphetamine (poly-drug) dependent mice using a conditioned place preference (CPP) model. The net pharmacological effects of buprenorphine/naltrexone treatment combination are agonism at the kappa opioid receptor and a partial agonist at the NOP receptor. Thus, this recent study aimed to investigate if the NOP receptor is the key opioid receptor that is responsible in attenuating relapse to this poly-drug addiction.